The Human Rights In Islam (The Study of Al-Muwafaqat by Imam Al-Syathibi) - Moch. Cahyo Sucipto (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2018)
The zhahiriyyah school is a school that stores certain texts by forgetting the global objectives of sharia. Among them there are those who are more dominant with the nature of religion, and among them there are those who are dominant in the nature of politics, even though they are all the same in terms of understanding literalism. The Zhahiriyya have been exaggerated in extracting text literalism to bring them to the strange understanding rejected by religion and reason. Zahiriyyah characteristics literal understanding and interpretation in understanding and interpreting texts without seeing things hidden in them, both in illat form and intentions that can be known by profound researchers: 1) Difficult and difficult; 2) Arrogant towards their opinions; 3) Don't accept different people; 4) Kafir people who have different opinions; 5) Whatever slander. The Bathiniyyah school is the opposite of the forgotten zhahiriyah school, even deliberately refusing, certain texts. This flow claims that they see the common good and global goals. This flow dares to oppose religious texts brought by the revelation ma`sum, both the Qur'an or al-Sunnah. They reject the text without caring, and freeze it without knowledge and guidance unless they follow the nature of themselves or others who want to make slander against the teachings of truth revealed by God. When they annulled religious texts in the name of human benefits. They claim that from these spies they are not out of the Shari'ah, they defend their intentions and maintain their spirit and substance, even though they do not maintain symbols and forms. Characteristics of the divine; 1) Superficial understanding of sharia `ah; 2) Dare to think without knowledge; 3) Follow westward. The third characteristic of the bathiniyyah school is to follow the other, west, both capitalism, liberalism or marix, all born in the west. From this they want to impose Western philosophy on the life, western views of religion, the concept of western scularism, and western, social, political, linguistic, and cultural legal theories for us. Some of them said,